Peace Education and Religious Moderation from Buya Syafi'i's Perspective: A Socio-Cultural Study - Helwa, Lina Af’ida Fataya; Fakhiroh, Zakiyatul (Proceeding International Conference on Religion, Science and Education, 2025)
Conflict and violence, and even war, continue to characterize various regions of the world. In Indonesia, various conflicts have occurred, including the Ambon and Maluku conflicts, the Poso conflict, the Bali bombings by terrorism, and other conflicts with religious undertones. As a multicultural country, Indonesia often experiences intercultural tensions and conflicts that affect social harmony. This research aims to explain the role of Peace Education and Religious Moderation according to Buya Syafi'i, a prominent figure known for his contributions to religious plurality in Indonesia. This study is a library research that relies on literature sources. The conclusion of this article is that in a multicultural society, it is essential to have multicultural understanding and awareness that respects differences, diversity, and a willingness to interact with others fairly. A moderate attitude in religion, with a humanistic approach, is needed—one that recognizes the existence of others, upholds tolerance, respects differing opinions, and refrains from imposing one’s views through violence. Additionally, enhancing Islamic education within the framework of peace education plays an important role in fostering tolerance.